Universal Design for Learning in Online Education: A Systematic Review of Evidence-Based Practice for Supporting Students with Disabilities - Utami, Iga Setia; Ghufron, Anik; Ishartiwi , Ishartiwi (International Journal of Learning, Teaching and Educational Research, 2025)
Every student should receive high-quality education from educational institutions that embrace inclusive teaching models. UDL, or the Universal Design for Learning, is the foundation that guarantees equitable education. Integrating UDL principles into online education enhances accessibility and equal access for students with disabilities. However, there is limited research on applying UDL in online learning environments to support such students. This study involved the conducting of an in-depth review of the existing literature to explore how UDL principles are implemented in online settings to support students with impairments. A literature search was performed across three databases (Scopus, ScienceDirect, and ERIC), and 14 articles were selected from an original pool of 360 based on the inclusion and exclusion criteria. The studies were analyzed following the PRISMA statement method, which consists of the identification, screening, eligibility, and inclusion stages. The findings explained how UDL has been implemented in online education and its influence on students with disabilities. The analysis revealed a notable gap in the empirical research on integrating UDL within virtual education, particularly in the special education context. These insights emphasize the urgent need for tailored professional development and deliberate resource allocation to enhance UDL implementation in virtual learning environments. https://doi.org/10.26803/ijlter.24.3.5